Assessment of teacher performance in a private Iranian high school using the North Carolina teacher performance appraisal instrument - Babaei, Davood; Rahimian, Hamid; Ahmad, Aminah; Bonakdar, Mohammad Hossein; Ziaeiane, Mohammad (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
This study assessed teachers' performance in a private Iranian high school using the Teacher Performance Appraisal Instrument (TPAI) of North Carolina. The teacher performance appraisal system was used to: 1) determine levels of competency, 2) improve performance, 3) validate strong performance, 4) professional growth plans, 5) identify areas needing improvement, 6) licensure, 7) document problems areas 8) accurately reflect performance, and 9) self assessment. In this study, a team of researchers scrutinized and assessed school teachers' performance in class. There were 31 teachers and they were assessed based on 8 major functions, further defined by 43 indicators. According to the findings, the teachers of the high school were divided into three groups: 1) teachers who mastered new instructional methods and had more than 10 years experience in teaching 2) teachers with 5 to 10 years of experience and 3) student teachers with less than 5 years background. The performance level of the first group was high in a majority of the functions. The performance level of the second group was high in some of the major functions and the third group showed low performance in a majority of the functions.